The New American Realism. - Carey, Martin (Worcester : Worcester Art Museum, 1965)
Dine, Jim ; Drexler, Rosalyn ; Indiana, Robert ; Johns, Jasper ; Lichtenstein, Roy ; Mallary, Robert ; Marisol ; Morris, Robert ; Oldenburg, Claes ; Rauschenberg, Robert ; Rivers, Larry ; Rosenquist, James ; etc.
The New American Realism, Worcester Art Museum, Worcester, February 18 through April 4, 1965
Engels
kunstcatalogus
Keywords: Amerika